Use of the insect encrustation technique in resin as a didactic tool for teaching and learning biology (Research, Society and Development, 2021)
Polymer fixed materials are increasingly used as instructional models, due to its strength, practicality, ease of handling and resemblance to the real object of study, allowing the understanding of the external morphological aspects of the specimens. Therefore, we verified the effectiveness of the method, through the technique of incrustation of arthropods, in the teaching-learning process of third-year high school students. Initially, a questionnaire was applied, evaluating the students' prior knowledge, on the external morphology of arthropod specimens. Then, a class was given with the models, allowing the manipulation and visualization of the copies. Finally, the students answered the initial questionnaire again, verifying and validating the process. The data obtained were transformed into percentage and presented in graphs, indicating that the models contributed to the understanding of arthropod structures. Therefore, this technique, if used by teachers, acts effectively in the teaching-learning process of students.